Effect of Arabica Coffee Production And Marketing Of Community Income In Sub-District Lolo District Solok Coast Mirror - Yeni, Fatma; Erita, Yeni; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This study aimed to determine the effect of arabica coffee production and marketing of the income of the people in sub-district Lolo Solok District Coast Mirror.The study was descriptive correlational. The population in this study all arabica coffee farmers in the Lolo District Nagari Coast Mirror, amounting to 654 farmers. Samples were taken with a random sampling proportional to the proportion of 15%, so the total sample of 89farmers.The research found that: 1) there is a significant effect on the income of arabica coffee production in the Lolo District village Coast Mirror for t calculate > t table (8.029> 1.662), including the influence of strong (r = 0.652) and a significant contribution (42.6 %), (2) there is a significant effect on the income of arabica coffee marketing community in sub-district Lolo District Coast Mirror for t calculate > t table (4.136> 1.662), the influence of marketing including moderate (r = 0.405) and a very small contribution (16.4% ) and (3) there is a significant effect of arabica coffee production and marketing of arabica coffee together against the income of the people in sub-district Lolo District Coast Mirror because F calculate > F table (44.168> 2.712), the influence of these two variables on income communities in village Lolo Mirror Coastal districts including strong category (r = 0.712) with a significant contribution (50.7%).